Journal of Greek Archaeology Volume 3: Editorial - Bintliff, John (Journal of Greek Archaeology, 2018)
True to our initial aims, this volume runs the whole chronological range of Greek Archaeology, while including every kind of material culture. We start with an overview of the major project of Nena Galanidou and her colleagues, investigating Palaeolithic environments, human settlement and other activities in the Ionian Islands.